PTU-147 Structured gastroenterological evaluation and improved outcomes for patients with chronic gastrointestinal symptoms following pelvic radiotherapy. (28th May 2012) - Henson, C C; McLaughlin, J; Ang, Y; Babbs, C; Crampton, J; Kelly, M; Lal, S; Limdi, J; Whatley, G; Swindell, R; Makin, W; Davidson, S E
Abstract : Introduction: 17 000 patients are treated with radical pelvic radiotherapy per year in the UK. 50% will develop chronic gastrointestinal (GI) symptoms that adversely affect quality-of-life, which have been shown to persist at the same level of severity for at least 3 years following treatment. Despite this, fewer than 20% are referred to a gastroenterologist. We aimed to determine if structured gastroenterological evaluation improves symptoms this patient group. Methods: 60 patients with GI symptoms ≥6 months after radical pelvic radiotherapy were identified from oncology clinics. Those requiring urgent investigation via the 2-week wait pathway were excluded. They were assessed at baseline using patient-reported symptom-based questionnaires: inflammatory bowel disease questionnaire (IBDQ); Vaizey incontinence questionnaire (VIQ); and the Common Terminology Criteria for Adverse Events (CTCAE) pelvis questionnaire. Participants were then referred to and managed by gastroenterologists using an algorithmic approach, which involves the identification of all GI symptoms and investigation for all potential causes for these symptoms. Further assessments were made at 3 and 6 months using the questionnaires. Results: 20 men and 36 women were included, with a median age of 58.5 years (range 26.9–81.8). Median time from radiotherapy to baseline gastroenterological assessment was 3.0 years (range 0.6–18.7). Median IBDQ score improved from 168 at baseline to 195 at 6 months (p=0.014). Median IBDQ bowel subset score improved from 41 at baseline to 50 at 6 months (p<0.0005). Significant improvement was also found in the median VIQ score from 11 at baseline to 8 at 6 months (p<0.0005). The median CTCAE rectum bowel mean score for men improved from 1.4 at baseline to 0.9 at 6 months and for women from 1.4 at baseline to 1.3 at 6 months. Pooling male and female data, the CTCAE mean score significantly improved comparing baseline with 6 month scores (p=0.001). Conclusion: GI symptom questionnaire scores significantly improved from baseline to 6 months. This suggests that structured gastroenterological evaluation using an algorithmic approach may improve GI symptoms in this patient group, although a controlled study is necessary to confirm this. Competing interests: None declared.